Geological Modeling of Sandstone Formations and Petrophysical Characterization of Hydrocarbon Reservoirs in the Termit Basin, Eastern Niger: Case of the Goumeri Prospect - Sarki, Laouali Ibrahim; Dodo, Bohari Abdou; Morabo Okoletimou, Vitaline Vanessa; Harouna, Moussa (European Scientific Journal, ESJ, 2023)
This study focuses on the geological model of sandstone formations and the petrophysical characterization of hydrocarbon reservoirs in the Termit Basin. The specific objectives are: (1) to establish a geological model visualizing the geometry of reservoir rocks and (2) to visualize the spatial and vertical distribution of the petrophysical parameters (porosity, permeability). The methodological approach integrated the interpretation of lithology data and petrographic parameters from the logs by using Petrel software 17.4 versions. The interpretation of the obtained results shows that: the reservoir formations present in the shape of sand lenses whose thickness varies according to another prospect. The petrophysical parameter models including the porosity and permeability model were used to understand the vertical and spatial distribution of the different reservoir units.